2016
DOI: 10.1063/1.4971332
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the electroluminescence of organic light-emitting diodes via fringe fields from patterned magnetic domains

Abstract: We predict very large changes in the room-temperature electroluminescence of thermally-activated delayed fluorescence organic light emitting diodes near patterned ferromagnetic films. These effects exceed the changes in a uniform magnetic field by as much as a factor of two. We describe optimal ferromagnetic film patterns for enhancing the electroluminescence. A full theory of the spin-mixing processes in exciplex recombination, and how they are affected by hyperfine fields, spin-orbit effects, and ferromagnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…34,45,46 However, the significant increase in FWHM of the Type I device indicates the existence of a potential new spin flip mechanism called DB mechanism, which is caused by an induced fringe magnetic field. 30,34,45 The potential DB mechanism may partially reduce the population of the polarons spinning flip via Dg mechanism, 47 which also possibly results in a decrease in MEL. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…34,45,46 However, the significant increase in FWHM of the Type I device indicates the existence of a potential new spin flip mechanism called DB mechanism, which is caused by an induced fringe magnetic field. 30,34,45 The potential DB mechanism may partially reduce the population of the polarons spinning flip via Dg mechanism, 47 which also possibly results in a decrease in MEL. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Engineered fringe field was first mentioned in MFE response of Alq 3 -based OLED having a structured FM electrode . Subsequently, magnetic fringe field control of the MFE response in OLEDs have been studied using different FM films. Spatially inhomogeneous magnetic fringe field was believed to be responsible for these phenomena. Ref dubbed this mechanism as “Δ B mechanism”.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that applying external magnetic fields to fluorescent, phosphorescent, and thermally activated delayed fluorescent (TADF) OLEDs can enhance their performance. [15][16][17][18][19][20][21][22][23] Various models have also been proposed to explain the observed magnetic field effects in these devices. These models mainly rely on the perturbation of the quantumstatistical 1:3 singlet-to-triplet exciton density ratio, [15][16][17][18][19][20][21][22] or on the reduced spin-dependent reaction rate between triplet excitons and polarons under external magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] Various models have also been proposed to explain the observed magnetic field effects in these devices. These models mainly rely on the perturbation of the quantumstatistical 1:3 singlet-to-triplet exciton density ratio, [15][16][17][18][19][20][21][22] or on the reduced spin-dependent reaction rate between triplet excitons and polarons under external magnetic fields. 23,24 While all the previous studies have mainly focused on enhancing the electroluminescence (EL) intensity and magneto-conductivity of OLEDs, to our knowledge, there has been no report on the influence of external magnetic fields on suppression of the external quantum efficiency (EQE) roll-off to date.…”
Section: Introductionmentioning
confidence: 99%